Rancang Bangun Alat Penyortir Barang menggunakan Barcode Berbasis Mikrokontroler - Perdian Pramana; Riki Mukhaiyar (Ranah Research : Journal of Multidisciplinary Research and Development, 2022)
Along with the development of increasingly sophisticated technology, information and communication in all fields, the level of consumer demand for services is becoming greater. By predicting the current background and reality, as long as the wheels of trade keep turning, the shipping service industry, especially those concerning packages or goods, is still sought after and needed. Before the goods or packages are delivered to the destination address by the courier, the incoming goods will first be sorted based on the courier's work area. The sorting process is still done manually using human power. Therefore, this research designed a sorting tool for goods based on the barcode printed on the goods. As many as 10 times testing this tool there is no error at all. Sorted items have been placed in place.